Answer:
x-2
x decreased by 2 equals x-2.
Have a nice day!!!!!!!!!! :-)
KA
Lucia ordered 3 pizzas for delivery, and the total cost is $27.89. The pizza arrived quickly, so Lucia wants to tip the delivery person 20%. How much is the tip?
What was the total cost for the pizza including the tip?
Answer:
Total cost =$33.47 Tip=$5.58
Step-by-step explanation:
$27.89÷5=5.578 5.578 rounded up to 2 digits=$5.58
$27.89+$5.58=$33.47
total cost is $33.47 tip=$5.58
Lucia should tip $5.58 for a 20% tip on her $27.89 pizza order. The total cost including the tip is $33.47.
To compute the tip Lucia should give for her pizza delivery, we need to calculate 20% of the total cost of the pizzas, which is $27.89. We first convert the percentage into decimal form by dividing 20 by 100, which gives us 0.20. Then we multiply this decimal by the total cost of the pizzas:
Tip = 0.20 imes $27.89 = $5.578
Since we usually round money to the nearest cent, the tip would be approximately $5.58. Now, to find the total cost including the tip, we add the tip to the original total:
Total Cost = Original Cost + Tip
Total Cost = $27.89 + $5.58 = $33.47
Therefore, the total amount Lucia would pay for the pizzas, including a 20% tip, is $33.47.
25 points for this question
1. Set Y to 0, solve for x. Then X can be any number greater than the answer.
y = -1.5x +7.5
0 = -1.5x +7.5
Subtract 7.5 from both sides:
-7.5 = -1.5x
Divide both sides by -1.5
X = -7.5 / -1.5x = 5
X > 5
2. The equation is the same as the first one, but now they want Y to be less than 0, so the answer would be the reverse of the first answer:
X < 5
1. Set Y to 0, solve for x. Then X can be any number greater than the answer.
y = -1.5x +7.5
0 = -1.5x +7.5
Subtract 7.5 from both sides:
-7.5 = -1.5x
Divide both sides by -1.5
X = -7.5 / -1.5x = 5
X > 5
2. The equation is the same as the first one, but now they want Y to be less than 0, so the answer would be the reverse of the first answer:
X < 5
Complete the factorization of 4x2 – 9.
4x2-9= ( x-
x+ )
Answer:
1.) 2
2.) 3
3.) 2
4.) 3
Step-by-step explanation:
9. Find the missing value in the equation.
3/4- blank/3=5/12
Answer:
[tex]\large\boxed{\dfrac{3}{4}-\dfrac{1}{3}=\dfrac{5}{12}}[/tex]
Step-by-step explanation:
[tex]\dfrac{3}{4}-\dfrac{\boxed{\ }}{3}=\dfrac{5}{12}\\\\\bold{METHOD\ 1:}\\\\LCD=12\\\\\dfrac{3\cdot3}{4\cdot3}-\dfrac{4\cdot\boxed{\ }}{4\cdot3}=\dfrac{5}{12}\\\\\dfrac{9}{12}-\dfrac{4\boxed{\ }}{12}=\dfrac{5}{12}\\\\\dfrac{9-4\boxed{\ }}{12}=\dfrac{5}{12}\iff9-4\boxed{\ }=5\qquad\text{subtract 9 from both sides}\\\\-4\boxed{\ }=-4\qquad\text{divide both sides by (-4)}\\\\\boxed{\ }=1[/tex]
[tex]\bold{METHOD\ 2:}\\\\\dfrac{3}{4}-\dfrac{\boxed{\ }}{3}=\dfrac{5}{12}\qquad\text{subtract}\ \dfrac{3}{4}\ \text{from both sides}\\\\-\dfrac{\boxed{\ }}{3}=\dfrac{5}{12}-\dfrac{3}{4}\\\\-\dfrac{\boxed{\ }}{3}=\dfrac{5}{12}-\dfrac{3\cdot3}{4\cdot3}\\\\-\dfrac{\boxed{}}{3}=\dfrac{5}{12}-\dfrac{9}{12}\\\\-\dfrac{\boxed{\ }}{3}=-\dfrac{4}{12}\\\\-\dfrac{\boxed{\ }}{3}=-\dfrac{1}{3}\to\boxed{\ }=1[/tex]
Radius of cone 15cm in height and 16cm in length
Final answer:
The curved surface area of a cone with a radius of 15 cm and a slant height of 16 cm is 753.982 cm², calculated using the formula A = πrl.
Explanation:
The question asks for the curved surface area of a cone with a given radius and slant height. To find the curved surface area of a cone, we use the formula:
A = πrl
where A is the area, π is pi (approximately 3.14159), r is the radius, and l is the slant height of the cone.
Here, the radius (r) is 15 cm and the slant height (l) is 16 cm. Substituting these values into the formula, we get:
A = π × 15 cm × 16 cm
A = 3.14159 × 15 cm × 16 cm
A = 753.982 cm²
Therefore, the curved surface area of the cone is 753.982 cm².
Solve for x.
0 = 7x² + x + 5
a x=−1±i139‾‾‾‾√14
b x=−1±i105‾‾‾‾√14
c x=−1±i34‾‾‾√14
d x=−1±i120‾‾‾‾√14
Answer:
[tex]a \: \: x = \frac{ -1 ± i\sqrt{139}}{14} [/tex]
Explanation:
Since this is unfactorable, use the Quadratic Formula:
[tex]x = -b ± \frac{ \sqrt{ {b}^{2} - 4ac}}{2a} [/tex]
Now, take the information and input it:
[tex] -1 ± \frac{ \sqrt{1 - 4(7)(5)}}{2(7)} \\ \\ -1 ± \frac{ \sqrt{ -139}}{ 14} = \frac{-1 ± i\sqrt{139}}{14} [/tex]
I am joyous to assist you anytime.
20 points if you answer right !!!!!HELP PLEASE
An experiment was conducted to test the following hypothesis it rains more in California then it doesn’t Arizona which of the following would show confirmation bias A.experiment suppose the hypothesis B.The scientist ignores Arizona desert because she doesn’t think it rains thereC.Experiment focuses equally on each states rainfall D. experiment prove a hypothesis to be true
Answer:
B
Step-by-step explanation:
When Experimenting scientist must include every part of the experiment and not leave out details.
Answer:b
Step-by-step explanation:
Simplify the square root of 5 times the cube root of 5.
five to the five sixths power
five to the one sixth power
five to the two thirds power
five to the seven sixths power
Answer:
Option 3 - five to the two thirds power
Step-by-step explanation:
Given : Expression 'the square root of 5 times the cube root of 5'.
To find : Simplify the expression ?
Solution :
Writing expression in numeric form,
The cube root of 5 means [tex]\sqrt[3]{5}[/tex]
The square root of 5 times the cube root of 5 means [tex]\sqrt{5\sqrt[3]{5}}[/tex]
Now, simplify the expression
[tex]\sqrt{5\sqrt[3]{5}}=\sqrt{5\times (5)^{\frac{1}{3}}}[/tex]
[tex]\sqrt{5\sqrt[3]{5}}=\sqrt{(5)^{1+\frac{1}{3}}}[/tex]
[tex]\sqrt{5\sqrt[3]{5}}=\sqrt{(5)^{\frac{4}{3}}}[/tex]
[tex]\sqrt{5\sqrt[3]{5}}=((5)^{\frac{4}{3}})^{\frac{1}{2}}[/tex]
[tex]\sqrt{5\sqrt[3]{5}}=(5)^{\frac{4}{3}\times \frac{1}{2}}[/tex]
[tex]\sqrt{5\sqrt[3]{5}}=(5)^{\frac{2}{3}}[/tex]
The expression is five to the two thirds power.
Therefore, Option 3 is correct.
The correct option is d. To simplify [tex]\(\sqrt{5} \cdot \sqrt[3]{5}\)[/tex], we get [tex]\(5^{5/6}\)[/tex]. Therefore, the correct answer is five to the seven sixths power.
To simplify [tex]\( \sqrt{5} \times \sqrt[3]{5} \)[/tex], we combine the radicals:
[tex]\[ \sqrt{5} \times \sqrt[3]{5} = 5^{1/2} \times 5^{1/3} \][/tex]
Using the property of exponents [tex]\( a^m \times a^n = a^{m+n} \)[/tex]:
[tex]\[ 5^{1/2} \times 5^{1/3} = 5^{1/2 + 1/3} \][/tex]
Now, find a common denominator for the exponents:
[tex]\[ \frac{1}{2} + \frac{1}{3} = \frac{3}{6} + \frac{2}{6} = \frac{5}{6} \][/tex]
Therefore,
[tex]\[ 5^{1/2} \times 5^{1/3} = 5^{5/6} \][/tex]
So, the simplified expression is [tex]\( {5^{5/6}} \).[/tex]
This corresponds to option (d) in your choices: five to the seven sixths power.
The complete question is- Simplify the square root of 5 times the cube root of 5.
a. five to the five sixths power
b. five to the one sixth power
c. five to the two thirds power
d. five to the seven sixths power
why can't 1.07 pounds of sugar be compared to 1.23 cups of sugar?
Answer:
A pound is a measure of weight and a cup is a measure of volume.
Step-by-step explanation:
You can't directly compare 1.07 pounds of sugar to 1.23 cups of sugar because they're measured in different units -- weight and volume -- and without a conversion factor (like density), they're not directly comparable. The solution is to convert one measurement to the other, such as by knowing that one cup of granulated sugar typically weighs about 0.44 pounds.
Explanation:The reason you can't directly compare 1.07 pounds of sugar to 1.23 cups of sugar is because they're measured in two different units -- weight and volume, respectively. Without a known conversion factor (in this case, the density of sugar), you can't equate the two. It's like comparing apples to oranges, the two quantities just aren't compatible without some more information.
Let's consider a real-world example. Just like you can't compare how heavy an object is to how much space it takes up without knowing the material's density, the same goes for comparing sugar in pounds and cups.
The solution is to convert one measurement to the other. For instance, by knowing that one cup of granulated sugar typically weighs about 200 grams (or 0.44 pounds), you could convert your weights and volumes to make a meaningful comparison.
Learn more about Converting Measurements here:https://brainly.com/question/34081145
#SPJ2
please help
find the perimeter of the polygon with the verdices u(-2,4),v(3,4) and w(3,-4) round to the nearest hundredth
the perimeter is about _______ units
Answer:
22.43 units
Step-by-step explanation:
we know that
The perimeter of a polygon is the sum of its length sides
the formula to calculate the distance between two points is equal to
[tex]d=\sqrt{(y2-y1)^{2}+(x2-x1)^{2}}[/tex]
we have
u(-2,4),v(3,4) and w(3,-4)
step 1
Find the distance uv
substitute the values
[tex]d=\sqrt{(4-4)^{2}+(3+2)^{2}}[/tex]
[tex]d=\sqrt{(0)^{2}+(5)^{2}}[/tex]
[tex]uv=5\ units[/tex]
step 2
Find the distance vw
substitute the values
[tex]d=\sqrt{(-4-4)^{2}+(3-3)^{2}}[/tex]
[tex]d=\sqrt{(-8)^{2}+(0)^{2}}[/tex]
[tex]vw=8\ units[/tex]
step 3
Find the distance uw
substitute the values
[tex]d=\sqrt{(-4-4)^{2}+(3+2)^{2}}[/tex]
[tex]d=\sqrt{(-8)^{2}+(5)^{2}}[/tex]
[tex]uw=\sqrt{89}=9.43\ units[/tex]
step 4
Find the perimeter
[tex]P=uv+vw+uw=5+8+9.43=22.43\ units[/tex]
Answer: The perimeter is about 22.43 units
Step-by-step explanation:
The circle graph shows how Lelia spends her day.
25%
School
10%
Homework
5% Soccer
40%
Sleeping
20%
Family Time
What percent of Lelia's day is spent on homework and school?
A 10%
B. 25%
C: 30%
D.35
E 40%
Answer:
D. 35%
Step-by-step explanation:
Note the percentage of each. You are trying to solve for the combination of homework and school.
In this case,
Homework = 10% of the pie chart.
School = 25% of the pie chart.
Add the two numbers together:
10 + 25 = 35
35% is your answer, or D).
~
Answer:
35%
Step-by-step explanation:
she spends 25% at or on school, and 10% on homework. all together (by adding) she spends 35%
If Ed can paint the bedroom by himself in 3 hours, and his friend , Jake, works at the same pace as Ed does , how long will it take to paint the room if the boys work together?(shoe work)
Answer:
1.5
Step-by-step explanation:
1 person = 3 hours
2 people = 1.5 hours
Answer:
1 hour and 30 minutes
Step-by-step explanation:
Each one of them needs 3 hours to paint the bedroom,but now they are 2 people who work at the same place so together,they only need half of the time.
give that Tan^2 0=3/8 what is the value of sec0?
The value of sec(θ) given [tex]\tan^2(\theta) = \frac{3}{8}[/tex] is [tex]\frac{\sqrt{22}}{4}[/tex]. Using the identity [tex]\tan^2(\theta) + 1 = \sec^2(\theta)[/tex], we find [tex]\sec(\theta) = \frac{\sqrt{22}}{4}[/tex].
To find the value of sec(θ) given that [tex]\tan^2(\theta) = \frac{3}{8}[/tex], we'll use the trigonometric identity:
[tex]\[ \tan^2(\theta) + 1 = \sec^2(\theta) \][/tex]
Given that [tex]\(\tan^2(\theta) = \frac{3}{8}\)[/tex], we can plug this into the identity:
[tex]\[ \frac{3}{8} + 1 = \sec^2(\theta) \][/tex]
[tex]\[ \frac{3}{8} + \frac{8}{8} = \sec^2(\theta) \][/tex]
[tex]\[ \frac{11}{8} = \sec^2(\theta) \][/tex]
To find [tex]\(\sec(\theta)\)[/tex], we take the square root of both sides, but since sec(θ) is always positive, we'll take the positive square root:
[tex]\[ \sec(\theta) = \sqrt{\frac{11}{8}} \][/tex]
[tex]\[ \sec(\theta) = \sqrt{\frac{11}{8}} \times \frac{\sqrt{8}}{\sqrt{8}} \][/tex]
[tex]\[ \sec(\theta) = \sqrt{\frac{88}{64}} \][/tex]
[tex]\[ \sec(\theta) = \frac{\sqrt{88}}{\sqrt{64}} \][/tex]
[tex]\[ \sec(\theta) = \frac{\sqrt{88}}{8} \][/tex]
[tex]\[ \sec(\theta) = \frac{2\sqrt{22}}{8} \][/tex]
[tex]\[ \sec(\theta) = \frac{\sqrt{22}}{4} \][/tex]
So, the value of [tex]\(\sec(\theta)\)[/tex] given [tex]\(\tan^2(\theta) = \frac{3}{8}\)[/tex]is [tex]\(\frac{\sqrt{22}}{4}\)[/tex].
Complete Question:
Given that tan²(θ) = 3/8, what is the value of sec(θ)?
The value of sec(θ) given that tan²(θ) = 3/8 is (1/4)√22.
To find the value of sec(θ) given that tan²(θ) = 3/8, we first need to recall the relationship between tangent (tan) and secant (sec) functions.
The relationship is as follows:
[tex]\[ \tan^2(\theta) + 1 = \sec^2(\theta) \][/tex]
Given that [tex]\( \tan^2(\theta) = \frac{3}{8} \),[/tex] we can substitute this value into the equation above:
[tex]\[ \left(\frac{3}{8}\right) + 1 = \sec^2(\theta) \][/tex]
Now, let's simplify the expression:
[tex]\[ \frac{3}{8} + 1 = \frac{3}{8} + \frac{8}{8} = \frac{3 + 8}{8} = \frac{11}{8} \][/tex]
So, [tex]\( \sec^2(\theta) = \frac{11}{8} \).[/tex]
Now, to find the value of sec(θ), we take the square root of both sides:
[tex]\[ \sec(\theta) = \sqrt{\frac{11}{8}} \][/tex]
To rationalize the denominator, we multiply both the numerator and the denominator by [tex]\( \sqrt{8} \):[/tex]
[tex]\[ \sec(\theta) = \frac{\sqrt{11 \times 8}}{\sqrt{8 \times 8}} = \frac{\sqrt{88}}{8} \][/tex]
Now, we can simplify the expression under the square root:
[tex]\[ \sqrt{88} = \sqrt{4 \times 22} = 2 \sqrt{22} \][/tex]
So, the final expression for sec(θ) is:
[tex]\[ \sec(\theta) = \frac{2 \sqrt{22}}{8} \][/tex]
And if we simplify it further, we get:
[tex]\[ \sec(\theta) = \frac{\sqrt{22}}{4} \][/tex]
This is the final answer for the value of sec(θ) in terms of the given information.
The Complete Question:
Given that tan²(θ) = 3/8, what is the value of sec(θ)?
11. (-7,-12,0, 5,2,-4,-1) least to greatest
Answer:
-12, -7, -4, -1, 0, 2, 5
Step-by-step explanation:
The larger a negative number the less value it actually has, whereas the larger a positive number the more value it has. You can think about it as if someone has taken something from you. If I take $12 from you you have less money than if I were to only take $7 from you. With positive numbers, you would have more money if I gave you 5 dollars than if I only gave you 2 dollars. You will always have more money if I give you money than if I were to take away money, that is why positive numbers are greater than negative numbers.
Hey!
------------------------------------------------
[tex]\large\boxed{-12, -7, -4, -1, 0, 2, 5}[/tex]
------------------------------------------------
Explanation:
The larger the negative number the smaller it is.
-12 < -7
-7 < -4
-4 < -1
The larger the whole number the greater it is.
0 < 2
2 < 5
------------------------------------------------
Hope This Helped! Good Luck!
12 hundredths = how many tenths and hundredths
7(x+2)=2x-1 solve for the variable
Answer:
x = - 3
Step-by-step explanation:
Given
7(x + 2) = 2x - 1 ← distribute parenthesis on left side
7x + 14 = 2x - 1 ( subtract 2x from both sides )
5x + 14 = - 1 ( subtract 14 from both sides )
5x = - 15 ( divide both sides by 5 )
x = - 3
The next number in the sequence -5, -2, 4, 13 is 25. Is this conjecture true or false?
Answer:
False
Step-by-step explanation:
The sequence seems to be increasing by 3+3(-5+3=-2, -2+3+3=4, so on). By 13, the sequence is increasing by 11, making the next number 24.
Answer:
the answer is true
Step-by-step explanation:
I just took the test and put false it was wrong
Determine the slope of the line that passes through the points (8,0) and (-3, 9).
Answer: 9/11
Step-by-step explanation: (8,0) (-3, 9). Subtract x values, subtract y values. This is known as delta x and delta y. Slope is rise/run. When you subtract the two points, you are finding the different between them. You're able to plug these x values and y values into an equation and get the correct answer. If you substitute x in, you get y. If you substitute y in, you get x (if you simplify it to get x on one side). So, the change is y is on the top, and change in x is on the bottom. 9 is divided by 11. This is the slope. You can plot this point by rising 9 and running (x axis) 11.
For which equation would x = 1 not be a solution?
x/1 = 1
x/2 = 2/4
x/3 = 3
x/4 = 1/4
Answer:
[tex] \frac{x}{3} = 3[/tex]
Step-by-step explanation:
[tex] \frac{1}{3} ≠ 3; \: \frac{9}{3} = 3[/tex]
I am joyous to assist you anytime.
Final answer:
The equation for which x = 1 is not a solution is x/3 = 3, as substituting x with 1 gives 1/3, which is not equal to 3.
Explanation:
To determine which equation x = 1 would not be a solution for, we need to substitute x with 1 in each equation and see if it holds true:
x/1 = 1: Substituting x with 1 gives us 1/1 = 1, which is true. Therefore, x = 1 is a solution.
x/2 = 2/4: Substituting x with 1 gives us 1/2 = 2/4, which simplifies to 1/2 = 1/2, also true. Hence, x = 1 is a solution.
x/3 = 3: Substituting x with 1 gives us 1/3 = 3, which is false, because 1/3 is not equal to 3. Therefore, x = 1 is not a solution here.
x/4 = 1/4: Substituting x with 1 gives us 1/4 = 1/4, which is true. Thus, x = 1 is a solution.
The equation for which x = 1 is not a solution is x/3 = 3.
The first two steps in the derivation of the quadratic formula by completing the square are shown below.
Which answer choice shows the correct next step?
Step 1: ax^2+ bx+c = 0
Step 2: ax^2 + bx=-c
Answer:
The correct next step is the answer choice
[tex]x^{2} +\frac{b}{a}x=-\frac{c}{a}[/tex]
Step-by-step explanation:
we have the quadratic equation in standard form
[tex]ax^{2}+bx+c=0[/tex]
The steps in the derivation of the quadratic formula by completing the square are
step 1
[tex]ax^{2}+bx+c=0[/tex] ----> given equation
step 2
Move the constant term over to the right-hand side
[tex]ax^{2}+bx=-c[/tex]
step 3
The leading term is multiplied by a
so
Divide by a both sides
[tex]x^{2} +\frac{b}{a}x=-\frac{c}{a}[/tex]
step 4
Multiply the linear term by 1/2
[tex]\frac{b}{a}(\frac{1}{2})=+\frac{b}{2a}[/tex]
step 5
square this derived value
[tex]+\frac{b^2}{4a^2}[/tex]
step 6
Add this squared value to either side of the equation
[tex]x^{2} +\frac{b}{a}x+\frac{b^2}{4a^2}=-\frac{c}{a}+\frac{b^2}{4a^2}[/tex]
step 7
convert to the common denominator, and combine on the right-hand side
[tex]x^{2} +\frac{b}{a}x+\frac{b^2}{4a^2}=\frac{b^2-4ac}{4a^2}[/tex]
step 8
convert the left-hand side to completed-square form
[tex](x+\frac{b}{2a})^{2}=\frac{b^2-4ac}{4a^2}[/tex]
step 9
take the square roots of either side
[tex](x+\frac{b}{2a})=(+/-)\sqrt{\frac{b^2-4ac}{4a^2}} \\\\(x+\frac{b}{2a})=(+/-)\frac{\sqrt{b^2-4ac}}{2a}[/tex]
step 10
solving for the variable
[tex]x=-\frac{b}{2a}(+/-)\frac{\sqrt{b^2-4ac}}{2a}\\\\x=\frac{-b(+/-)\sqrt{b^2-4ac}}{2a}[/tex]
Answer:
C on edge
Step-by-step explanation:
what are x- and y intercepts for the graph of 5x-2y=20 brainly.com
Answer:
(4, 0 ) and (0, - 10 )
Step-by-step explanation:
To find the x- intercept let y = 0 in the equation
5x - 0 = 20
5x = 20 ( divide both sides by 5 )
x = 4 ← x- intercept ⇒ (4, 0 )
To find the y- intercept let x = 0 in the equation
0 - 2y = 20
- 2y = 20 ( divide both sides by - 2 )
y = - 10 ← y- intercept ⇒ (0, - 10 )
The x- and y-intercepts of the equation 5x - 2y = 20 are 4 and -10 respectively. The x-intercept is obtained by setting y = 0, likewise, the y-intercept is obtained by setting x = 0.
Explanation:The x-intercept and y-intercept of an equation can be found by setting the other variable to zero and solving for the remaining variable. In the equation 5x - 2y = 20:
To find the x-intercept, we set y = 0, thus, the equation becomes 5x = 20. Solving for x, we get x = 4. To find the y-intercept, we set x = 0, so the equation becomes -2y = 20. Solving for y, we get y = -10.
So, the x-intercept is 4 and the y-intercept is -10 for the given equation.
Learn more about x- and y-intercepts here:https://brainly.com/question/32051056
#SPJ12
Paul wants to gift wrap the boxes. He has 1,000.00 square inches of wrapping paper. Does Paul have enough to wrap all three boxes?
Answer:
y
Step-by-step explanation:
Jonathan tries to mathematically model the number of seats in a given row. He tries to come up with an
equation for the number of seats and determines:
S = 7r+2, where S is the number of seats in row,
Does this equation work for r=1? What about for r = 2 and r = 32 Show calculations that support
your yes/no answers.
- please help * I’m a freshman and I suck at math *
Answer:
Yes it does
Step-by-step explanation:
Why because “r” it means rows there could 1- infinite rows so S=7r (7 it means that each row has 7 seats) so let’s say r=2 (remember that is the # of rows are) so S=7(2)+ 2 (we replace r=2 on X) so 7•2=14 S=14+2=16 soo there are S=16 like 16 seats in 2 rows hope this could help y you understand....
Fill in the blank to make the following statement true: 1,426 centigrams = _____ kilograms
A : 0.01426
B : 14.26
C : 1.426
D : 0.1426
Answer: A. 0.01426
Step-by-step explanation:
divide the mass value by 100000
Answer:
A. 0.01426
Step-by-step explanation:
divide by 10000
The sum of a number squared and 15
Answer:
x^2+15
Step-by-step explanation:
The statement, The sum of a number squared and 15 is n² + 15.
What is a numerical expression?A numerical expression is a mathematical statement written in the form of numbers and unknown variables. We can form numerical expressions from statements.
Given, The sum of a number squared and 15.
let the number be 'n'.
∴ The statement, The sum of a number squared and 15 can be formed numerically as,
n² + 15.
we can also convert numerical expressions into statements.
learn more about numerical expressions here :
https://brainly.com/question/29199574
#SPJ2
write an expression for the quantity X less than 2? A.) x-2 B.) 2-x C.) x+2
Answer:
B
Step-by-step explanation:
The way the question is worded, you start with the 2. Two is the first number to be written. It is awkwardly worded, but that is how it begins. Then you take x away from it.
2 - x
B
Simplify the following expression. 2^2 • 2^3
The simplification of the expressions give above would be = 32
How to simplify the given expression?To simplify the given expression the following steps needs to be taken as follows:
2²× 2³
Where;
2² = 2×2
2³ = 2×2×2
The simplification = 2×2×2×2×2= 32
Learn more about multiplication here:
https://brainly.com/question/29793687
#SPJ2
Which of the following is a composite number?
A. 61
B. 111
C. 263
D. 307
can someone explain how to know if a number is composite and prime
Answer:
B.111
Step-by-step explanation:
111 is a composite number because the number can be divided evenly by more numbers than 1 and itself.
how to get 654 divided by 3 with partial quotients
Answer:
218 every part
Step-by-step explanation:
654/3 = 218
Zoe decided to measure the hand length of each of her classmates. First she marked a line across each student's wrist and lined up a ruler from this mark to the top of the middle finger to measure the length. Then she recorded the measurements in the table below.
Answer:
the ruler is marked in centimeters, but Zoe recorded data in ruler
Step-by-step explanation:
I just checked and I got it right
Answer: A. The ruler is marked in centimeters, but Zoe recorded data in inches.
Step-by-step explanation: I got a 100% on this quiz